PENGARUH PENERAPAN DISIPLIN TERHADAP PRESTASI KERJA (KASUS KARYAWAN HOTEL RESTY MENARA PEKANBARU) - Emil Budi Utomo; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aimed to determine the implementation of discipline to employee workachievement by Resty Menara Hotel Pekanbaru. Work discipline as an independentvariable (X) and employee work achievement as the dependent variable (Y), and thisstudy took a number of respondents were 43 respondents. Data obtained through thequestionnaire and then further processed to be tested through statistical analysis such asa simple regression analysis, t test, and correlation analysis and determination with thehelp of using the SPSS 16 for windows application. The results provethat theimplementation of discipline to employee work achievement in Resty Menara HotelPekanbaru has done well.Keywords: Discipline, work achievement